Target miss using PTV-based IMRT compared to robust optimization via coverage probability concept in prostate cancer. (2nd August 2020) - Outaggarts, Zoulikha; Wegener, Daniel; Berger, Bernhard; Zips, Daniel; Paulsen, Frank; Bleif, Martin; Thorwarth, Daniela; Alber, Markus; Dohm, Oliver; Müller, Arndt-Christian
Abstract: Purpose: Cure- and toxicity rates of prostate IGRT can both be affected by ill-chosen planning target volume (PTV) margins. For dose-escalated prostate radiotherapy, we studied the potential for organ at risk (OAR) sparing and compensation of prostate motion with robust plan optimization using the coverage probability (CovP) concept compared to conventional PTV-based IMRT. Material and methods: We evaluated plan quality of CovP-plans for 27 intermediate risk prostate cancer patients treated in a prospective study (78 Gy/39 fractions). Clinical target volume (CTV) and OARs were contoured on three separate CTs to capture movement and deformation. To define the internal target volume (ITV), the union of CTV1-3 was encompassed by an isotropic margin of 7 mm for the planning process. CovP-dose distribution is optimized considering weight factors for IMRT constraints derived from probabilities of systematic organ displacement in the three CTs. CovP-dose volume histograms (DVHs) were compared with additionally calculated conventional PTV-based IMRT plans. PTV-based IMRT was planned on one-single CT with an isotropically expanded CTV to generate the PTV (i.e., CTV1 + 7mm) and was evaluated on the two other CTs. Results: The CovP-concept showed higher robustness in target volume coverage. Target miss was frequently observed with PTV-based IMRT, resulting in cold spots until 70 Gy with the CovP-concept. The target dose at 74 Gy was comparable, while further the dose–escalation (75–78 Gy) was improved with PTV-based IMRT. However, dose–escalation with PTV-based IMRT was associated with increased OAR-doses, especially in high-dose areas. Conclusions: Probabilistic dose-escalated IMRT was feasible in this prospective study. Comparison of the CovP-concept with PTV-based IMRT revealed superiority with regard to target-coverage and sparing of OARs. The CovP-concept implements a robust plan optimization strategy for organ deformation and motions and could, therefore, serve as a less demanding compromise on the way to adaptive IGRT avoiding daily time-consuming re-planning. SUMMARY We evaluated the robustness of coverage probability (CovP)-based IMRT plans within a prospective study for prostate cancer radiotherapy. The treatment plans were compared with newly calculated conventional PTV-based IMRT plans. We were able to show that CovP led to a clearly more robust target coverage by avoiding hot spots at OARs compared to conventional PTV-based IMRT. In addition, negative consequences of an inflated PTV can be ameliorated by a more relaxed CovP-based dose prescription.